VD_FINDINFO HC / 2011 / 269 vom 17. Mai 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, SUSPENSION DE LA PROCÉDURE, COMPENSATION DE CRÉANCES | 124 al. 1 CO, 257d CO, 265 CO, 274g al. 1 let. a CO, 123 al. 1 CPC, 123 al. 2 CPC, 124a CPC, 2 CPC, 347 let. c CPC, 457 CPC, 15 al. 1 LPEBL, 23 LPEBL, 25 LPEBL, 29 LPEBL, 86a TFJC, 404 al. 1 CPC (CH)